2012
DOI: 10.5194/amt-5-2993-2012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the quality of OSIRIS mesospheric temperatures using satellite and ground-based measurements

Abstract: The Optical Spectrograph and InfraRed Imaging System (OSIRIS) on the Odin satellite is currently in its 12th year of observing the Earth's limb. For the first time, continuous temperature profiles extending from the stratopause to the upper mesosphere have been derived from OSIRIS measurements of Rayleigh-scattered sunlight. Through most of the mesosphere, OSIRIS temperatures are in good agreement with coincident temperature profiles derived from other satellite and ground-based measurements. In the altitude r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
(39 reference statements)
0
16
0
Order By: Relevance
“…The temperature data also exhibit a cold bias of 10-15 K near 85 km (Sheese et al, 2011) (the upper boundary of the Rayleighscatter-derived temperatures) and a cold bias of 5-15 K near 48 km due to multiple scattering effects not taken into account in the retrieval. However, between 55 and 80 km, these temperatures are valid and are typically within 4-5 K of other satellite data (Sheese et al, 2012).…”
Section: Osiris Datamentioning
confidence: 52%
See 1 more Smart Citation
“…The temperature data also exhibit a cold bias of 10-15 K near 85 km (Sheese et al, 2011) (the upper boundary of the Rayleighscatter-derived temperatures) and a cold bias of 5-15 K near 48 km due to multiple scattering effects not taken into account in the retrieval. However, between 55 and 80 km, these temperatures are valid and are typically within 4-5 K of other satellite data (Sheese et al, 2012).…”
Section: Osiris Datamentioning
confidence: 52%
“…A comparison with these temperatures is therefore not included here. Instead, OSIRIS temperatures derived from the O 2 A-band emission spectra near 762 nm (see Sheese et al, 2010Sheese et al, , 2012, for details) are used. Temperature data are available between 45 and 110 km, but temperatures between 80 and 86 km are deemed unreliable, due to uncertainties in O 2 absorption in the A-band.…”
Section: Osiris Datamentioning
confidence: 99%
“…Shepherd et al (2001) determined temperature profiles from 65 to 90 km during the period March 1992 -January 1994 analysing WINDII/UARS data at 553nm. More recently Sheese et al (2012) retrieved temperature profiles using OSIRIS/Odin bright limb observations at 318.5 and 347.5 nm in the altitude range 45-85 10 km. In the frame of the ESA funded MesosphEO project, a new dataset of temperature profiles in the altitude range 35-85 km was created from the analysis of GOMOS/ENVISAT bright limb observations in the spectral band 420-480 nm.…”
Section: Mls (Microwave Limb Sounder On the Aura Satellite) And Sabermentioning
confidence: 99%
“…OSIRIS retrieved temperature profiles were compared to SABER, SOFIE, ACE-FTS v2.2, and ACE-FTS v3.0 (Sheese et al, 2012). Comparison with ACE-FTS found that ACE-FTS was 9 K warmer at 48 km but less than 3 K warmer between 60 and 80 km.…”
Section: Ace-fts Data Setsmentioning
confidence: 99%